Aflatoxins: Contamination of animal feeds and food products - Randall K. Phebus (Kansas Agricultural Experiment Station Research Reports, 1993)
Mycotoxins are toxic chemicals produced by certain species of molds during their growth on numerous substrates. Molds can invade the food and feed supply at various points throughout production, storage, processing, and distribution. Of most concern are the aflatoxins, which are highly toxic and classified as probable human carcinogens. Aflatoxins are often associated with crops that have undergone stress or feeds and foods that have been stored improperly. Tremendous economic implications are associated with regulation, testing, and loss of agricultural products from aflatoxin contamination. Dairy cattle excrete a portion of consumed aflatoxins into milk, thus, leading to a strict action level of 0.5 ppb in fluid milk. Several types of processed food products have been demonstrated to be occasionally contaminated with these toxins.; Dairy Day, 1993, Kansas State University, Manhattan, KS, 1993;
Keywords: Dairy Day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-149-S; Report of progress (Kansas Agricultural Experiment Station); 694; Dairy; Aflatoxins; Molds; Carcinogens; Toxins; Federal regulations